Work Stress as a Mediator between Work-Family Conflict and Work Burnout among Female Employees in the Garment Industry - Zulfa Rahmalia; Maharani Tyas Budi Hapsari (Psikoislamedia: Jurnal Psikologi, 2026)
This study was conducted to examine the importance of work stress in explaining the relationship between work-family conflict and work burnout among female employees in the garment industry. High work demands and family roles make female employees prone to work fatigue, so work-family conflict is expected to increase work burnout through work stress. This study used a quantitative approach with 114 female employees who were housewives working in the production department of the garment industry as subjects. Data were collected using the work-family conflict scale, job stress scale, and Maslach Burnout Inventory (MBI) scale, which had been adapted to the research context. Data analysis was performed using the Hayes PROCESS Macro Model 4 with the help of IBM SPSS version 22. The results showed that work–family conflict had a significant effect on work stress and work burnout, and work stress acted as a partial mediator in this relationship. These findings emphasize the importance of organizational and social support in helping female employees balance their work and family roles.